2013
DOI: 10.1530/joe-13-0027
|View full text |Cite
|
Sign up to set email alerts
|

HPA axis changes during the initial phase of psychosocial stressor exposure in male mice

Abstract: Chronic subordinate colony (CSC) housing for 19 days results in unaffected basal morning corticosterone (CORT) levels despite a pronounced increase in adrenal mass, likely mediated by an attenuation of adrenal corticotropin (ACTH) responsiveness. Given that the pronounced increase in basal morning plasma CORT levels returns to baseline as early as 48 h after the start of CSC, it is likely that the attenuated ACTH responsiveness develops already during this initial phase. This was tested in the present study. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In addition to the above described data assessed on day 20 of CSC (after 19 days of CSC), a time course analysis revealed that relative adrenal mass was significantly increased in stressed mice at all time-points assessed (24, 48 h, days 7, 14, 20) during the 19 days of CSC exposure ( 130 ). A more recent study, confirming the increase in relative adrenal weight following 48 h of CSC, extended these findings to demonstrate that even 10 h of CSC are sufficient to cause such changes ( 134 ). However, in contrast to relative weight, absolute adrenal weight during this initial phase of CSC was increased after 10 h, but not 48 h, of CSC exposure.…”
Section: Chronic Subordinate Colony Housingmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition to the above described data assessed on day 20 of CSC (after 19 days of CSC), a time course analysis revealed that relative adrenal mass was significantly increased in stressed mice at all time-points assessed (24, 48 h, days 7, 14, 20) during the 19 days of CSC exposure ( 130 ). A more recent study, confirming the increase in relative adrenal weight following 48 h of CSC, extended these findings to demonstrate that even 10 h of CSC are sufficient to cause such changes ( 134 ). However, in contrast to relative weight, absolute adrenal weight during this initial phase of CSC was increased after 10 h, but not 48 h, of CSC exposure.…”
Section: Chronic Subordinate Colony Housingmentioning
confidence: 73%
“…So far, the CSC model has reproducibly been shown to work in different mouse strains, namely, C57BL/6 mice ( 130 ), BALB/c mice ( 132 ), and CD1 mice ( 41 ). Moreover, CSC effects are independent from the background of the residents, as the physiological, immunological, and behavioral consequences of the CSC paradigm are comparable using either C57BL/6 ( 130 ) or the male offspring of CD1 female mice [bred at the Max Planck Institute of Psychiatry in Munich (Germany) for high anxiety-related behavior (HAB mice)] and male C57BL/6 mice as dominant animals ( 133 , 134 ). Recent own unpublished data reveal that using male CD1 mice as residents allows reliable reproduction of known CSC effects (see Figure 2 ).…”
Section: Chronic Subordinate Colony Housingmentioning
confidence: 99%
“…One possible explanation for these trends is that at both 24 hr time points and the 1.5 wks time point, the HPA had already become desensitized, potentially involving attenuated release of pituitary ACTH and/or reduced adrenal responsiveness [ 54 ]. However, at these earlier times of higher allostatic load, glucocorticoid-programing of muscle and liver may have been already put them into a heightened state for mobilizing amino acids and producing glycogen.…”
Section: Resultsmentioning
confidence: 99%
“…However, supplementation with LBP for 30 days markedly reduced blood lipid levels in the HL and HLS groups, as compared with that in the H group. A previous study demonstrated that the hypothalamic pituitary adrenal axis, the sympathetic adrenal medullary axis and the renin-angiotensin-aldosterone system were all capable of releasing large quantities of stress hormones following chronic composite psychological stress, including catecholamine, adrenal cortical hormone, glucagon, thyroxine and rennin (19). Catecholamine and adrenal cortical hormone have previously been shown to decrease the scavenging ability of TG on vascular endothelial cells by inhibiting lipoprotein lipase activity.…”
Section: Discussionmentioning
confidence: 99%